The Impact of Audio-Visual Educational Media on Infant Basic Immunization Adherence at Rum Balibunga Primary Health Center - Tika Nofiyanti Iskandar; Tut Rayani Aksohini Wijayanti (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Background: Compliance with routine infant immunization is essential for the success of vaccination programs and the prevention of vaccine-preventable diseases. However, adherence to immunization schedules remains suboptimal due to limited parental knowledge, concerns about vaccine safety, and the limited effectiveness of conventional health education. Audio-visual media offer a promising solution by delivering information in a more engaging, clear, and consistent manner. Objective: This study aimed to evaluate the effectiveness of audio-visual educational media in improving adherence to basic immunization among infants in the service area of the Rum Balibunga Community Health Center. Methods: A quasi-experimental design with a one-group pretest-posttest approach was used. The sample included 40 mothers with infants aged 0-12 months selected through purposive sampling. Participants received an educational video on basic immunization. Adherence was assessed before and after the intervention based on completeness and timeliness according to the national schedule. Data were analyzed using univariate and bivariate methods, with the McNemar test for paired categorical data. Results: There was a significant improvement in immunization adherence after the intervention. Statistical analysis confirmed a meaningful difference before and after exposure, indicating the effectiveness of audio-visual media. Conclusion: Audio-visual education is an effective strategy to improve infant immunization adherence and can be widely applied in primary healthcare settings.